Soil aggregates and carbon distribution in tectona grandis (linn. f.) plantation, Nigeria (2017)
Soil and tree biomass are reservoir for carbon but there is uncertainty regarding their influence on soil carbon stabilization. Carbon associated with clay size aggregate is considered a major determinant of soil carbon accumulation. However, other aggregates are becoming relevant in the estimation of soil carbon accumulation. These limit the detail carbon estimation of soil. Therefore, soil carbon accumulation of aggregate sizes was estimated at two soil depths in Tectona grandis plantation. Six (30 x 30m2) plots were randomly demarcated in the plantation and 360 topsoil and subsoil samples were used for this study. Soil core samples were collected at five points at depths of 0-15, 15-30 cm in each plot for period of six months. Soil core samples collected were oven dried at 105 0C. Soil sample (100g) from each core sample was sieved into >2.0, 2.0-1.0, 1.0-0.5, 0.5-0.050 and <0.050 mm aggregate sizes using dry sieve procedure and proportions weighed. A subsample of 10g of each fraction was combusted in Muffle furnace at 500 0C for 4 hours and carbon content estimated. Carbon content of the bulk soil was also determined. Data were analysed using descriptive statistics, regression analysis at α0.05 The 0.5-0.05 mm fraction had the highest proportion of soil at top and subsoil (39 and 28%, respectively). Aggregate size of <0.05 mm had the highest soil carbon concentration at topsoil and subsoil. Exponential and logistic equations performed better on the basis of R2, F-value and Standard Error of Estimate. Therefore, carbon content of 0.5-0.05 and 1.0-0.5 mm aggregates accurately estimate carbon content of topsoil and subsoil using the exponential equation. Carbon content of fine silt size aggregate (0.5-0.05 mm) determined carbon accumulated. Exponential model of soil carbon is determined by the aggregate size distribution of each soil layer.